Nanoencapsulation platform for oral delivery of peptides: In vitro stabilization of AvPAL and formulation of a gastrointestinal-resistant luciferase - Daniel Abella-López; Adrián López-Teijeiro; Tomás Pose-Boirazian; Natalia Barreiro-Piñeiro; José M. Martínez-Costas (Materials Today Bio)
Phenylketonuria (PKU) is a genetic metabolic disorder caused by an enzyme deficiency that leads to the accumulation of phenylalanine, which can cause neurotoxicity and several other problems. A potential alternative to the universal standard treatment based on a lifelong protein-restricted diet, is the development of oral replacement therapies using phenylalanine ammonia lyase from Anabaena variabilis (AvPAL). However, oral administration of polypeptides presents a major challenge due to gastrointestinal (GI) instability. To address this issue, the use of the IC-Tagging system as an advanced one step, in cellulo nanosphere (NS)-encapsulation strategy for protein stabilization and oral delivery is proposed. A highly active version of AvPAL was produced to which nanoencapsulation provides formidable thermostability, resistance to acidic pH, long-term storage stability and protection against proteolytic degradation. This latter characteristic, essential for oral delivery of polypeptides, is further enhanced by coating with chitosan the NS-encapsulated enzyme. Thus, a similarly nanoencapsulated and chitosan-coated luciferase displays sustained enzymatic activity through the entire GI transit when administered orally in mice, indicating the high protective capability of the system while maintaining the availability of the enzyme. Overall, these results highlight the potential and versatility for peptide-based oral delivery applications of this innovative methodology.